Pravni vidiki zakonske zveze v rimskem pravu - Novak, Aleš (Keria (Ljubljana), 1999)
The author's intent is to present a clear and accurate a survey of legal regulation regarding marriage in Roman law. First, the author deals with certain preconditions, which had to be met in order a marriage could at all take place: conubium, maturity and consensus (of both partners and their patres familias). The first step towards marriage was sponsalia - betrothal, which had (unlike today) certain legal consequences. In Roman law there were two types of marriage: marriage cum manu and sine manu, the main difference being in wife's legal status. In marriage cum manu wife came under the manus of her husband, whereas in marriage sine manu her father kept manus over her. The author then briefly describes confareatio, coemptio and usus, three basic forms of marriage which had to be observed in order a lawful marriage to be constituted. At the end the author discusses the question of dissolution of marriage (divorce, death, deportation, captivity).
Keywords: družinsko pravo; pravna zgodovina; rimsko pravo; zakonska zveza